2014
DOI: 10.1039/c4nr04083j
|View full text |Cite
|
Sign up to set email alerts
|

Do dislocations act as atomic autobahns for oxygen in the perovskite oxide SrTiO3?

Abstract: The transport properties of edge dislocations comprising a symmetrical 6° [001] tilt grain boundary in weakly acceptor-doped SrTiO3 were investigated by means of various experimental and computational techniques. Oxygen transport along the dislocation array was probed by means of (18)O/(16)O exchange experiments under (standard) oxidising conditions (pO2 = 5 × 10(-1) bar) and also under reducing conditions (pO2 = 7 × 10(-22) bar) at T = 973 K. In both cases, isotope profiles obtained by Secondary Ion Mass Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
156
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 80 publications
22
156
1
Order By: Relevance
“…3c, which has consistently been found from different dislocations along the boundary. This feature agrees well with the dissociated core structures proposed for the same type of edge dislocations [12,26]. Moreover, dissociation has also been found in other different types of dislocations [25,27].…”
Section: Atomic Structure Of Dislocation Coresupporting
confidence: 82%
“…3c, which has consistently been found from different dislocations along the boundary. This feature agrees well with the dissociated core structures proposed for the same type of edge dislocations [12,26]. Moreover, dissociation has also been found in other different types of dislocations [25,27].…”
Section: Atomic Structure Of Dislocation Coresupporting
confidence: 82%
“…By employing a concurrent atomistic continuum simulation Yang et al [95] also confirmed the importance of easy glide planes in SrTiO 3 resulting in a preference of the <110> directions for dislocation nucleation and revealed that the presence of an agglomeration of dislocations in form of bicrystalline boundaries in SrTiO 3 has a significant effect on the mechanical properties and the crack evolution [97]. Bicrystals have also been widely investigated in order to determine whether dislocations have an impact on the ionic transport of oxygen [45] or not [17]. By molecular dynamics simulations of dislocations it was found that the formation enthalpy of oxygen vacancies is significantly lower compared to the bulk [31].…”
Section: Molecular Atomic Simulationmentioning
confidence: 89%
“…[6][7][8][9][10] In order to systematically elucidate the microstructure-property relationships in perovskite oxides, dislocations at bicrystal grain boundaries have been extensively studied. [11][12][13] This is mainly because, as model systems, the type and the density of dislocations at bicrystal grain boundaries can be controlled to a large extent by adjusting the misorientation between the two crystal parts. Strontium titanate (SrTiO 3 ) is a representative perovskite oxide and is a well-known prototype material for resistive switching.…”
mentioning
confidence: 99%